A maiden application of Jaccard similarity for identification of tripped branch utilizing current synchronized measurement considering false data injection attack. (15th June 2022) - Alam, Mehebub; Kundu, Shubhrajyoti; Sankar Thakur, Siddhartha; Banerjee, Sumit
Highlights: The current measurement of PMUs are used instead of voltage measurements. The concept of Jaccard similarity is utilized to formulate a novel objective function. A generalized mathematical model of false data injection (FDI) attack is formulated considering two types of attack such as in phase attack and angular attack. The proposed method is validated to identify the tripping of parallel branches and case study of IEEE 57 bus is presented. The proposed method is implemented on different IEEE benchmark systems in MATLAB software. Abstract: The accurate identification of tripped branch (ITB) is an essential requirement to maintain the reliability and security of modern smart grid. Most of the existing phasor angle based approaches fail to identify the tripping of parallel branches. To this end, a novel method is presented in this study using current measurements of phasor measurement unit (PMU). A new term namely Jaccard dissimilarity index (JDI) is proposed and the ITB problem is solved through JDI based novel objective function. Furthermore, a generalized mathematical model of false data injection (FDI) attack is formulated considering two types of attack such as in phase attack and angular attack. Considering the FDI attack, the proposed method is implemented on different IEEE systems in MATLAB software. The identification rate of the proposed method is found to be competitive compared to some well-established methods. Test results considering various aspects such attack factor variation and attack location variation prove the applicability and effectiveness of the proposed method.